Why Do Children Who Solve False Belief Tasks Begin to Find True Belief Control Tasks Difficult? A Test of Pragmatic Performance Factors in Theory of Mind Tasks - Schidelko, Lydia P.; Huemer, Michael; Schröder, Lara M.; Lueb, Anna S.; Perner, Josef; Rakoczy, Hannes (Frontiers in Psychology, 2022)
The litmus test for the development of a metarepresentational Theory of Mind is the false belief (FB) task in which children have to represent how another agent misrepresents the world. Children typically start mastering this task around age four. Recently, however, a puzzling finding has emerged: Once children master the FB task, they begin to fail true belief (TB) control tasks. Pragmatic accounts assume that the TB task is pragmatically confusing because it poses a trivial academic test question about a rational agent’s perspective; and we do not normally engage in such discourse about subjective mental perspectives unless there is at least the possibility of error or deviance. The lack of such an obvious possibility in the TB task implicates that there might be some hidden perspective difference and thus makes the task confusing. In the present study, we test the pragmatic account by administering to three- to six-year-olds (N=88) TB and FB tasks and structurally analogous true and false sign (TS/FS) tasks. The belief and sign tasks are matched in terms of representational and metarepresentational complexity; the crucial difference is that TS tasks do not implicate an alternative nonmental perspective and should thus be less pragmatically confusing than TB tasks. The results show parallel and correlated development in FB and FS tasks, replicate the puzzling performance pattern in TB tasks, but show no trace of this in TS tasks. Taken together, these results speak in favor of the pragmatic performance account.